SCOUTING EDUCATION EXTRACURRICULAR PROGRAM IN FORMING STUDENTS' CHARACTER AT A STATE HIGH SCHOOL IN POSO CITY - Baya Tamin, Kalsum; Askar, Askar; Jihan, Jihan; Pettalongi, Adawiyah (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2023)
This article discusses the use of scouting education extracurricular program in forming students character at state senior high school in Poso city, Central Sulawesi. The research utilized a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The research findings indicate that the implementation of the extracurricular scouting education program at a Senior High School in Poso was based on the scouting extracurricular activity work program at the Senior High School. Routine activities include Enforcement Deliberation, Ambalan Working Council Meeting, Ambalan Guest Reception Camp, Scouting Material, Enforcement Test, and Scout Agility Competition. Additional activities include End of Year Camp. Participation/Complementary Activities include Social Activities and Regional Activities. The extracurricular scouting education program in shaping students' character impacts the formation of honest character, tolerance, and responsibility for the Senior High School students.